Instructional Management During Covid-19 - Astuti, Fitri; Arafat, Yasir; Furkan, Nuril (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to describe learning management and the inhibiting and supporting factors for learning during the Covid-19 pandemic. It is descriptive qualitative research. Data collection techniques using observation, interviews, and documentation. Data collection techniques use observation, interviews, and documentation. Data analysis techniques are data collection, data reduction, data display, and conclusions. The results of the study show that learning management during the Covid-19 pandemic at SMP Negeri 01 Semendawai, Suku Ill included planning, implementation, and evaluation. The learning planning is the preparation of Limited Face-to-face Learning, namely health protocol facilities, Covid-19 task force, Limited PTM supporting documents, preparation of learning tools Special Conditions Curriculum. The Learning implementation refers to the policy of the Head of Education and Culture Office of East OKU Regency regarding technical instructions Implementation of Limited PTM for the 2020/2021 school year. The learning evaluation is carried out normally according to the pandemic situation, namely the assessment of learning outcomes by teachers, education units, and the government. The inhibiting factor for learning is students’ enthusiasm for learning is low, the signal is not stable, and not all students have a smartphone. The supporting factors for learning are the enthusiasm of teachers, parents, and students to learn face-to-face, school discipline, good cooperation between school members, health protocol facilities, a Covid-19 handling task force, and the use of smartphones.